СООТНОШЕНИЕ ЭЛЕКТРОННЫХ И ПУБЛИЧНЫХ УСЛУГ В УКРАИНЕ - ЛЕГЕЗА, Евгений Александрович (SUPREMANCE OF LAW, 2016)
The scientific article is devoted to coverage of the category of e-services. Compared to the category «Administrative Services», «public service» and «municipal services». The main approaches to the definition of electronic services by public administrations and feature extraction above concepts.
Keywords: public services; administrative services; municipal services; e-services